Triple-Regimen of Vemurafenib, Irinotecan, and Cetuximab for the Treatment of BRAFV600E-Mutant CRC: A Case Report and Review - Cho, Su Min; Esmail, Abdullah; Abdelrahim, Maen (Frontiers in Pharmacology, 2021)
Mutation of the BRAF proto-oncogene is found in approximately 10% of colorectal cancers (CRC), with much of the mutation conferred by a V600E mutation. Unlike other CRC subtypes, BRAF-mutant CRC have had relatively limited response to conventional therapies and overall poor survival. We present the case of a 75-year-old man with severe nonischemic cardiomyopathy on a LifeVest who was found to have a transverse colonic mass with widespread hepatic metastatic disease and was subsequently found to have BRAFV600E-mutant CRC (MSI High/dMMR). After a failed therapy with FOLFOX and pembrolizumab, the patient was started on a regimen of vemurafenib, irinotecan, and cetuximab (VIC) based on the SWOG 1406 trial which had shown improved progression-free survival and response rate for the treatment of BRAFV600E-mutant metastatic CRC. After 40 cycles of VIC, the patient attained complete response and is in remission off chemotherapy with significant improvement. This case highlights the effectiveness of the triple-regimen of vemurafenib, irinotecan, and cetuximab as a treatment option for BRAFV600E-mutant CRC, which is a treatment regimen based on the SWOG 1406 trial, and also demonstrates the synergistic role of BRAFV600E inhibitors and EGFR inhibitors in the treatment of BRAFV600E-mutant CRC.